Effects of Defending: The Longitudinal Relations Among Peer‐perceived Defending of Victimized Peers, Victimization, and Liking. Issue 4 (6th May 2015) - Meter, Diana J.; Card, Noel A.
Abstract Previous research has shown victims of peer aggression to be positively impacted by being defended by peers, but how enacted defending impacts defenders themselves is not thoroughly understood. In this study, the longitudinal associations between peer‐perceived liking, enacted defending, and defender's own victimization were investigated among 336 adolescents (M age = 13.21 years). Peer perceived liking was expected to predict defending. It was also hypothesized that a reputation for defending victimized peers would be related to being perceived as less victimized and more liked over time. Results showed that peer perceived liking was not predictive of defending. Enacted defending was associated with a decrease in victimization over time, but also a decrease in peer‐perceived liking. Defenders may benefit from enacted defending by decreasing their own victimization, but this benefit is nuanced.